Impact of Ridge-Furrow Planting in Pakistan: Empirical Evidence from the Farmers Field - Imtiaz Hussain; Akhter Ali; Ansaar Ahmed; Hafiz Nasrullah; Badar ud Din Khokhar; Shahid Iqbal; Azhar Mahmood Aulakh; Atta ullah Khan; Jamil Akhter; Gulzar Ahmed (International Journal of Agronomy)
Wheat is planted through the broadcast method on 7.8 million ha and irrigated through low-efficiency flood basin irrigation methods. With decreased water availability, there is a need to adopt water use efficient planting techniques. The current paper uses two-year trials data set as well as farmer survey data to demonstrate benefits of ridge-furrow planting wheat and farmer perception regarding the technology in Pakistan. During 2014–15 and 2015–16, ridge-furrow planting of wheat was compared with farmer practice of planting on flat surface through broadcasting at 162 sites located in 15 districts of Pakistan. In a survey, 134 farmers shared their experiences about ridge-furrow planting. Data collected from field trials and demonstrations showed that better tillering and crop growth contributed towards 12% higher wheat grain yield with ridge-furrow planting in comparison with the farmer practice of flat planting in all 15 districts during both years. Furrow-irrigated ridge planting of wheat helped farmers in saving of 30–35% water in comparison with farmer practice. Farmers adopting ridge-furrow wheat planting earned USD 100.63 per hectare more profit than nonadopter farmers. Adoption of this technology on one million hectare can help in saving 1 million acre foot of water and produce additional 0.36 million tons of wheat per year.